1984
DOI: 10.2307/1191692
|View full text |Cite
|
Sign up to set email alerts
|

Better Living through Police Discretion

Abstract: The author wishes to give special thanks to participants in a seminar at the Centre for Criminological and Socio-Legal Studies, University of Sheffield, for their critical feedback on a draft of this paper, and to Vera Marsh and Andrew Vorder Bruegge for typing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Despite this congruence between Pepinsky's (1984) own appraisal of the situation and the subjects' reported perceptions, the author concluded the latter was exemplary of, "false presumptions of discretion by police" (p. 251). With respect to the officers' perception that, in the absence of formal guidance, they possessed substantial discretionary autonomy, Pepinsky concluded that "the officers were wrong" (p. 251).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Despite this congruence between Pepinsky's (1984) own appraisal of the situation and the subjects' reported perceptions, the author concluded the latter was exemplary of, "false presumptions of discretion by police" (p. 251). With respect to the officers' perception that, in the absence of formal guidance, they possessed substantial discretionary autonomy, Pepinsky concluded that "the officers were wrong" (p. 251).…”
Section: Introductionmentioning
confidence: 97%
“…More so, it necessarily raises the question of how to empirically disentangle the various determinants of police behavior. "Effective limits," some have argued, must necessarily include any structuring force operating upon the officer (Campbell, 1999;Pepinsky, 1984). Logically, even if legal limits could be usefully bracketed off from other determinants, to do so effectively reduces discretion to the absence of formal control.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations